Influence of ball position on playing space in Spanish elite women's football match-play - Zubillaga, A.; Gabbett, T. J.; Fradua, L.; Ruiz-Ruiz, C.; Caro, O.; Ervilla, R. (International Journal of Sports Science and Coaching, 2013)
The aims of this study were to examine the playing area in female football matches according to the position of the ball. We investigated: 1) the space between the two offside lines (the length), 2) the width, 3) the distance from the least advanced defender to the goal line in defensive activity, 4) the distance from the least advanced attacker to her goal line in attacking activity, 5) the distance between the goalkeeper and her nearest attacking team mate, and 6) the distance between the goalkeeper and her nearest defending team mate. With these measurements we were also able to obtain 7) the individual playing area used during female professional football matches. Data were collected during Spanish matches and notated post-event using the Amisco® system. A total of 2756 game situations were coded from four games. The distribution of players was significantly (p<0,001) wider and shallower when the ball was in the central areas of the field (37.07 m x 43.84 m "zone 3" and 36.36 m x 42.82 m "zone 4") than when the ball was in a "building up play" zone (43.31 m x 39.24 m "zone 1"), and the finishing and scoring zone (48.14 m x 39.80 m "zone 6"). The values obtained for the individual playing area varied between 77.91 m² and 96 m². The players stood further from the goals depending on the position of the ball. The spaces at the back of the defensive line changed from 45.75 m to 6.90 m (to the goal line) depending on the position of the ball. In addition, the spaces at the back of the less advanced attacking line changed from 16.45 m to 52.24 m, depending on the position of the ball. There were significant differences (p<0.05) in playing spaces between all zones. The results show that the spaces were significantly different depending on the ball position. Changes in playing space are presented as an important factor to consider when designing game-specific training activities for female football.